Nghiên cứu quá trình hấp phụ chất màu xanh metylen bằng diatomit Phú Yên: Động học, đẳng nhiệt hấp phụ và nhiệt động học - Khiếu, Đinh Quang; Hà, Trần Thái; Thiện, Trần Vĩnh (Vietnam Journal of Chemistry, 2012)
The study of the methylene blue adsorption from aqueous solution by Phu Yen diatomite was conducted in terms of kinetics, isotherme adsorption and thermodynamics. The study of methylene blue adsorption was conducted in batch condition. Kinetic data and equilibrium removal isotherms were obtained. The rate of methylene blue adsorption was well described by a second-order kinetic model. The adsorption isotherm of Langmuir model gave a better fit to the experimental data in comparison with the Frendlich molel. The maximum capacity of blue methylene adsorption is around 128.20 mg/g at 30oC. Thermodynamic study revealed that methylene blue adsorption is an endothermic process (DH = 4.12 kcal/mol) and the adsorption increase with an increase in temperature from 283 to 303 K.